2009
DOI: 10.1007/s12272-009-1413-9
|View full text |Cite
|
Sign up to set email alerts
|

Gingerol inhibits cisplatin-induced vomiting by down regulating 5-hydroxytryptamine, dopamine and substance P expression in minks

Abstract: To investigate the antiemetic effect of gingerol and its multi-targets effective mechanism on 5-hydroxytryptamine (5-HT), dopamine (DA) and substance P (SP). The antiemetic effect of gingerol was investigated on a vomiting model of mink induced by cisplatin (7.5 mg . kg(-1), i.p.) in 6 h observation. The levels of 5-HT, DA and distribution of substance P in the area postrema and ileum were measured by high performance liquid chromatography (HPLC) and immunohistochemistry respectively. The frequency of cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 34 publications
2
39
2
Order By: Relevance
“…Similar to other emesis models, like the ferret [35], we observed substance P immunoreactivity throughout the dorsal vagal complex. In contrast to the reported effect of cisplatin (7.5 mg/kg, ip) to induce an increase in substance P immunoreactivity in the AP of mink by 6 h [18], we did not observe any significant changes in staining in the AP, NTS or DMN of musk shrews, up to 30 mg/kg ip. We also observed no significant difference in substance P immunoreactivity in the spinal cord between saline and cisplatin treated shrews.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to other emesis models, like the ferret [35], we observed substance P immunoreactivity throughout the dorsal vagal complex. In contrast to the reported effect of cisplatin (7.5 mg/kg, ip) to induce an increase in substance P immunoreactivity in the AP of mink by 6 h [18], we did not observe any significant changes in staining in the AP, NTS or DMN of musk shrews, up to 30 mg/kg ip. We also observed no significant difference in substance P immunoreactivity in the spinal cord between saline and cisplatin treated shrews.…”
Section: Discussioncontrasting
confidence: 99%
“…We chose to focus on these areas because they are involved in generating the emetic reflex (hindbrain) and processing of pain signals (spinal cord); cisplatin treatment is known to produce both emesis and pain in patients [e.g., 16]. Substance P is the endogenous ligand for the NK 1 receptor [17], and cisplatin injection was reported to increase substance P immunoreactivity in the area postrema in mink [18]. In addition, we performed histological analysis of kidney toxicity at these timepoints, since renal toxicity is a common and clinically relevant side-effect of cisplatin treatment [19].…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis is that ginger competitively interacts with the same receptors that standard anti‐CINV medication acts upon, thereby reducing the binding rate of medications when used in combination . Animal studies support this hypothesis, indicating that gingerols and shoagoals are able to bind to both 5‐HT 3 and substance P receptors, which are the receptors with which medications such as aprepitant and ondansetron interact . It should also be noted that these studies showed that different ginger compounds bound to these receptors with varying strengths and, therefore, different preparations of ginger could exert differing effects on nausea.…”
Section: Discussionmentioning
confidence: 92%
“…Pungent arylalkanes (gingerols and shogaols) seem to be part of the active principle as they blocked these receptors in the low micromolar range . This is corroborated by studies in which the antiemetic effects of gingerols and shogaols were demonstrated in animal models . On the basis of these facts, we investigated the mode of action of ginger on human 5‐HT 3 receptors as rodents considerably differ from humans with regard to the 5‐HT 3 receptor system .…”
Section: Introductionmentioning
confidence: 78%